Repeated mild traumatic brain injury causes focal response in lateral septum and hippocampus. (25th May 2016) - Acabchuk, Rebecca; Briggs, Denise I; Angoa-Pérez, Mariana; Powers, Meghan; Wolferz, Richard; Soloway, Melanie; Stern, Mai; Talbot, Lillian R; Kuhn, Donald M; Conover, Joanne C
Aim: To advance our understanding of regional and temporal cellular responses to repeated mild traumatic brain injury (rmTBI), we used a mouse model of rmTBI that incorporated acceleration, deceleration and rotational forces.Materials & methods: A modified weight-drop method was used to compare two inter-injury intervals, rmTBI-short (five hits delivered over 3 days) and rmTBI-long (five hits delivered over 15 days). Regional investigations of forebrain and midbrain histological alterations were performed at three post-injury time points (immediate, 2 weeks and 6 weeks).Results: The rmTBI-short protocol generated an immediate, localized microglial and astroglial response in the dorsolateral septum and hippocampus, with the astroglial response persisting in the dorsolateral septum. The rmTBI-long protocol showed only a transitory astroglial response in the dorsolateral septum.Conclusion: Our results indicate that the lateral septum and hippocampus are particularly vulnerable regions in rmTBI, possibly contributing to memory and emotional impairments associated with repeated concussions.